Knowledge Management of Local Wisdom on Dulcimer Instruments to Development Life and Career Skills for Students in Thung Fai Subdistrict, Lampang Province - Kaewkongpan, Duangjan; Poommalee, Waraporn; Choothong, Chisapath; Senchanthichai, Siyaphat; Aunjit, Duangporn; Gatong, Somsak; Sriwichai, Kanokporn; Thaisuchat, Haruthai; Maneethong, Pronsawan (Interdisciplinary Academic and Research Journal, 2023)
Ban Mae Ta area, Thung Fai Subdistrict, Mueang District, Lampang Province is an area where groups gather to produce Thai musical instruments (Khim), which are unique to the village, and products that create jobs and income for the people of almost every household. The dulcimer-making occupational group was established in 1996 with local sages and dulcimer-making entrepreneurs. It is considered an outstanding and unique area of Lampang Province. This research article aimed to 1) manage local wisdom knowledge of dulcimer musical instruments, 2) promote the learning of local knowledge of dulcimer musical instruments to develop life and career skills for students, and 3) study the satisfaction of students towards learning the local wisdom of the dulcimer musical instrument to develop life and career skills for students in Thung Fai Sub-district, Lampang Province. This research was mixed-method which integrated quantitative Research and qualitative research. Target groups were local wisdom of dulcimer musical sages, Ban Mae Tha’s group of dulcimer entrepreneurs, educational institutions, and students in Thung Fai Subdistrict. The research tools were 1) a questionnaire, 2) an interview form, 3) a survey form, 4) a focus group discussion by collecting information from local sages, a group of dulcimer entrepreneurs and educational personnel in the area, and 5) a satisfaction questionnaire. Statistics for analyzing data were mean, and standard deviation which were presented with a table and description. And the qualitative data analysis was using open-ended questions which were analyzed by content analysis, then analyzed by categorized knowledge about the local knowledge of the dulcimer musical instrument that passed for accuracy from the experts. The results stated that; (1) the knowledge management of local wisdom on dulcimer musical instruments, in conducting knowledge management of local wisdom musical instruments which is a system for seeking knowledge, knowledge creation or innovation, and proper storage of knowledge to increase the efficiency of working knowledge of local knowledge of dulcimer musical instruments. (2) the promotion of learning local wisdom of dulcimer musical instruments can develop life skills and careers for students is a step that brings the knowledge gained from knowledge management of local knowledge of dulcimer musical instruments. designed to develop life and career skills for students. And (3) the satisfaction of the students about learning the local wisdom of the dulcimer musical instrument, it was found that the overall satisfaction was at a high level, and from qualitative analysis, it mentioned that the community can produce dulcimer musical instruments as a career and wants to inherit them to remain alive and also driven by the youth generation in community schools. Suggestions from this research were encouraging and drive in the teaching and learning curriculum to see the value of local wisdom that creates aesthetics for students by playing the community’s dulcimer instrument to soothe the mind and pride of the community.